Cognitive Decision Process: The Context of Auditors' Diagnostic Reasoning (Malaysian Management Journal, 1999)
Based on a cognitive psychology framework, this article provides an insight into how auditors perform diagnostic reasoning tasks through an analytical review (AR) process. AR refers to the diagnostic process of identifying, investigating, and resolving unexpected fluctuations in account balances and other financial relationships in financial statements. Auditors perfuming AR typically follow four distinct components of a diagnostic, sequential and iterative (DS1) process, namely: mental representation, hypothesis generation, information search, and hypothesis evaluation. Through the DS1 process, auditors are able to recognize and detect errors and irregularities in financial statements for the purpose of presenting a true and fair view of financial reporting, with the intention of communicating quality and reliable economic information of an enterprise to users.